Decision-Making Analysis Of Koi Pool Pump Selection Using Analytical Hierarchy Process (AHP) Method - Marni Astuti; Ramadhan Rafiq Ibrahim; Yasrin Zabidi; Riani Nurdin; Uyuunul Mauidzoh (Compiler, 2023)
The availability of various koi pond pump products is marketed with various kinds, types, and various advantages. This diversity makes it difficult for business owners to determine a koi pond pump product that suits their business needs. The consideration of the pump in question is a koi pond pump in the form of an electric submersible pump or ESP. One method that can be used for the selection of a koi pond pump is the AHP (Analytical Hierarchy Process) method. This study uses the AHP method assisted by expert choice software. From the results of the assessment of the importance of the criteria in the selection of suppliers, the priority scales are as follows: Priority I Brand Reputation (0.4251), Product Design (0.2661), Power Consumption (0.1102), Durability (0.1074), Ease of Maintenance (0.054), and Price (0.0409). From the results of the alternative assessment, the following priorities were generated: priority I Eheim CON12000 (0.4105), Resun PG12000 (0.2318), Yamano ACT12000 (0.2025), and Atman MP12000 (0.1551).